Band edge positions as a key parameter to a systematic design of heterogeneous photocatalyst - Abdullah, Eshraq Ahmed (European Journal of Chemistry, 2019)
Although, plenty of photocatalytic approaches have been developed in the past few decades to overcome major drawbacks, such as; wide band gap and fast volume/surface recombination of the charge carriers, the researchers still need to carry out careful systematic studies before conducting experiments based on physicochemical properties of a system. Thus, in this review, a detailed discussion of the band edge positions controlling the migration and charge separation of the produced charged carriers and its impact onto the photocatalytic systems are provided. The knowledge of band edge positions is a crucial prerequisite to a rational design of an efficient photocatalytic system. The enhancement mechanism should match these criteria to be reliable in the field of heterogeneous photocatalysis science.